2022
DOI: 10.13170/depik.11.3.25787
|View full text |Cite
|
Sign up to set email alerts
|

Biological aspects of Diopatra sp. (Onuphidae, Polychaeta) collected from mangrove habitats of Jeruklegi, Cilacap Regency

Abstract: Diopatra species are members of the family Onuphidae (Polychaeta, Annelida) that are widely used as fishing bait. These tubicolous worms are common in particular mangrove areas of Cilacap. However, biological aspects of Diopatra sp. inhabiting the areas have not been studied. In the present work, we investigated several biological aspects of the worms, including the segment number, the body weight and the sex ratio, based on Diopatra samples collected from four mangrove habitats of Jeruklegi Village, Cilacap R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In total, 22 individuals of Diopatra were examined. The lower number of individuals examined from Jeruklegi (2) was because most of the individuals collected from this village had been used in the study by Wibowo et al (2022). We found that all of these solitary tubeworms were identical to D. claparedii Grube, 1878.…”
Section: Resultsmentioning
confidence: 76%
“…In total, 22 individuals of Diopatra were examined. The lower number of individuals examined from Jeruklegi (2) was because most of the individuals collected from this village had been used in the study by Wibowo et al (2022). We found that all of these solitary tubeworms were identical to D. claparedii Grube, 1878.…”
Section: Resultsmentioning
confidence: 76%
“…(present study) also have the potential for use as feed in aquaculture due to their relatively high protein and fat contents. The latter two species, however, are still poorly studied despite an initial research on some biological aspects of Diopatra by Wibowo et al (2022). The identity of these three Javanese species also remains unknown to date that further taxonomic investigations are required; they may represent new records or even new species considering that polychaete taxonomic studies in the southern coast of Java have been limited (Pamungkas and Glasby, 2019).…”
Section: Macronutrient Contentsmentioning
confidence: 99%
“…Other Asian species include D. aciculata (Knox and Cameron, 1971) and D. sugokai (Izuka, 1907), in Japan, as well as D. claparedii Grube, 1878, in Malaysia. In Cilacap, Central Java Province, Indonesia, Diopatra worms are also used as fishing bait by local anglers (Wibowo et al, 2022) the animals are called 'lur umah' in the local language, which means a worm with housing. The worms were initially identified as D. neapolitana by Purwati et al (2020), but the occurrence of this European species in Indonesian waters is highly unlikely considering the long distance between the two geographic regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peta lokasi pengambilan sampel. Peta diedit dengan SimpleMappr (https://www.simplemappr.net) dan (Google Maps) dengan beberapa pengeditan(Wibowo et al 2022)…”
unclassified